RISK FACTORS IN HYPERTENSION - Tursunkulova D.Sh., (Central Asian Journal of Medicine, 2025)
Hypertension, or high blood pressure, is one of the most common chronic diseases in the modern world. This disease has a significant impact on the health of the heart and vascular system and can lead to many serious complications, including heart attack, stroke, kidney failure, and eye diseases. Hypertension is often called the “silent disease” because most patients do not know they have it for a long time, as there are no obvious symptoms in the early stages. Therefore, it is very important to identify and manage the risk factors for hypertension.